2019
DOI: 10.1111/imj.14187
|View full text |Cite
|
Sign up to set email alerts
|

Crohn's & Colitis Australia inflammatory bowel disease audit: measuring the quality of care in Australia

Abstract: Background Australia has among the highest prevalence of Crohn disease and ulcerative colitis in the world. Management of the chronic gastrointestinal disorders results in significant societal costs and the standard of care is inconsistent across Australia. Aim To audit the quality of care received by patients admitted for inflammatory bowel disease (IBD) across Australia against national IBD standards. Methods A retrospective cross‐sectional survey and clinical audit was undertaken assessing organisational re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 13 publications
0
54
0
Order By: Relevance
“…A previous Australian study using the same measure of distress (K10) ( n = 336) documented clinically significant levels in 52% of respondents. A national audit of IBD hospital care identified that “mental health condition” was the most common comorbid condition and affected more than a quarter of hospitalized patients. Less than a quarter of these patients received psychological support in hospital.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous Australian study using the same measure of distress (K10) ( n = 336) documented clinically significant levels in 52% of respondents. A national audit of IBD hospital care identified that “mental health condition” was the most common comorbid condition and affected more than a quarter of hospitalized patients. Less than a quarter of these patients received psychological support in hospital.…”
Section: Discussionmentioning
confidence: 99%
“…Data on patient needs and access to psychological services in IBD are scarce. A national audit of IBD hospital care found a major gap in the access to multidisciplinary services, including psychology support, but the data for mental health services outside inpatient care are lacking. The present survey was designed to describe the levels of distress in people with IBD, as well as the needs, attitudes, and access to psychological services for people with IBD in Australia against established Australian IBD Standards, which recommend psychological screening for all IBD patients, access to mental health services for inpatient assessment, and treatment and coordination of psychological treatment with primary care mental health services (Standard A13).…”
Section: Introductionmentioning
confidence: 99%
“…However, a recent national audit of hospital-and clinician-based IBD care led by Crohn's & Colitis Australia (CCA) found it to fall short of national standards. 6,7 A major gap was identified in access to multidisciplinary services, including psychological support. Of note, those IBD services with even a partial IBD-Team, defined as a clinical lead, some IBD nurse time and a helpline, provided improved care compared to those that did not.…”
Section: Introductionmentioning
confidence: 99%
“…There is growing international interest in quality improvement and benchmarking of IBD care within individual health care systems and between countries . The UK IBD Audit has served as a model for a recent national programme in Australia . However, the interpretation of trends in outcomes from serial UK audits is difficult owing to differences in site participation and case ascertainment between audit rounds and different hospitals.…”
Section: Introductionmentioning
confidence: 99%